Multiple brain abscesses from isolated cerebral mucormycosis. Issue 5 (May 1990) - Escobar, A; Del Brutto, O H
Abstract : A report is presented of a patient with cerebral mucormycosis without rhinosinusal or systemic evidence of the disease. The predisposing condition was drug-induced immunosuppression. Computed tomography (CT) showed focal areas of abnormal enhancement which correlated with necropsy findings of localised parenchymal brain damage; this represented encapsulated brain abscesses, a rare form of presentation of cerebral mucormycosis.